ANALYSIS OF MARKET TIMING TOWARD LEVERAGE OF NON-FINANCIAL COMPANIES IN INDONESIA - Wulandari, Vera Pipin; Setiawan, Kusdhianto (Journal of Indonesian Economy and Business, 2015)
ABSTRACTThis study aimed to examine the effect of market timing on leverage on non-financial compa-nies in Indonesia. Market timing was tested on the hot and cold market conditions. Hot and cold markets are determined by the monthly market to book ratio. A hot (cold) market occurs when the average market to book ratio of a particular month is above (below) the value of the moving average of the monthly market to book ratio. This study also aimed to test whether non-financial companies in Indonesia persistently applied leverage policies. This study used two research models. The first model was a panel data with a sample size of 77 non-financial companies listed on the Indonesian Stock Exchange from 2002-2013.The second model was a cross section data with a sample size of 157 non-financial companies that conducted their IPO in Indonesia from 2003-2013. The dependent variable in both the research models was leveraget (levt). The independent variables were markett and leveraget-1 (levtâ1). The control variables were profitabi-lityt-1 (proft-1); and sizet-1. The results of this study indicated that market timing affected the lev-erage of non-financial companies listed on the Indonesian Stock Exchange. However, market timing did not affect the leverage of non-financial companies that had their IPO in Indonesia. The non-financial companies in Indonesia were not persistently applying a leverage policy. The capital structure of non-financial companies in Indonesia changed because of the influence of variable profitability and size (which supports the pecking order and trade off theory).Keywords: market timing theory, leverage, hot and cold market, market to book ratio